Investigation of the synthesis, gelation potential, and drug-loading capacities of two novel amides - Bariş Cebe, Deniz; Kötekoğlu, Elif (Frontiers in Chemistry, 2024)
This study consists of four steps. In the first, two different biocompatible organogelators were synthesized, starting with the L-isoleucine amino acid to obtain amide compounds. In the second step, the gelation potential of synthesized organogelators with fatty acid esters and organic solvents was investigated. These esters were chosen as gelation liquids due to their biocompatibility and also their penetration-enhancing properties when the drug is administered via the skin. After the minimum gel concentrations (MGCs) of the organogelators were determined, the melting point of gel Tg was found, and then, ΔHg gelation enthalpy values were found by means of the Van’t Hoff equation. In addition to the gelation abilities and capacities of the organogelators being thus synthesized, their thermal stabilities were also determined. In the third stage of the study, the network which occurred during the formation of the gels was screened by an SEM device, and their characterizations were determined. In the study's fourth stage, the gels were loaded with ibuprofen and naproxen—known for their non-steroidal anti-inflammatory and analgesic effects—and their drug-loading capacities were thus determined.